2020
DOI: 10.1177/0361198120922212
|View full text |Cite
|
Sign up to set email alerts
|

A Correlated Random Parameters Model with Heterogeneity in Means to Account for Unobserved Heterogeneity in Crash Frequency Analysis

Abstract: Unobserved heterogeneity induced by omitted variables is a major challenge in developing reliable road safety models. In recent years, the random parameters negative binomial (RPNB) model has been used frequently in crash frequency analysis to account for unobserved heterogeneity. However, the majority of past studies of the RPNB model assumed that there was no correlation between different sources of unobserved heterogeneity, which is not always true given the complex interactions of safety factors. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Thailand has over 42 million registered vehicles, with motorcycles accounting for 50% of the total and being responsible for the majority of road fatalities [58], thus potentially contributing to the largest number of fatalities from significant accidents. As Jomnonkwao, Uttra and Ratanavaraha [2] observed, motorcyclists are responsible for the vast majority of road fatalities; meanwhile, prior studies showed different types of cars and motorcycles, such as SUV/vans [47], large trucks [40,47,49], and pick-ups [40], that have rolled over. Additional research on motorcycle riders specifically, as well as other types of road users, may be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thailand has over 42 million registered vehicles, with motorcycles accounting for 50% of the total and being responsible for the majority of road fatalities [58], thus potentially contributing to the largest number of fatalities from significant accidents. As Jomnonkwao, Uttra and Ratanavaraha [2] observed, motorcyclists are responsible for the vast majority of road fatalities; meanwhile, prior studies showed different types of cars and motorcycles, such as SUV/vans [47], large trucks [40,47,49], and pick-ups [40], that have rolled over. Additional research on motorcycle riders specifically, as well as other types of road users, may be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Islam, et al [35] highlighted that curved roads necessitate a reduction in speed, particularly in cases of high traffic volume, increasing the risk of rear-end collisions. Slope variation is another factor influencing the frequency of rear-end collisions, especially for trucks, due to brake-related issues when repeatedly applying the brakes [36]. Finally, the presence of median openings also contributes to the likelihood of rear-end collisions, as observed by Champahom, et al [37].…”
Section: Highway Geometric Design Features On the Frequency Of Truck-...mentioning
confidence: 95%
“…Many previous studies emphasized the importance of taking the unobserved heterogeneity into consideration while analyzing crash-related factors. Furthermore, random parameters logit (RPL) models [ 16 , 17 , 18 , 19 ], random parameters logit models with heterogeneities in the means [ 20 , 21 ], and random parameters logit models with heterogeneities in the means and variances [ 5 , 22 , 23 ] have all been successfully utilized in the investigation of crash injury-severity. Hence, to account for the unobserved heterogeneity, the random parameters logit model with heterogeneities in the means and variances was used in this study.…”
Section: Methodsmentioning
confidence: 99%